The Competitiveness, Bargaining Power, and Contract Choice in Agricultural Water Markets in Pakistan: Implications for Price Discrimination and Environmental Sustainability - Razzaq, Amar; Liu, Hancheng; Zhou, Yewang; Xiao, Meizhen; Qing, Ping (Frontiers in Environmental Science, 2022)
Pakistan is the world’s third-largest user of groundwater and the fourth-largest groundwater withdrawing country. The Indus Basin aquifer from where Pakistan withdraws its groundwater has become the world’s most “overstressed” groundwater aquifer. Given the growing shortages of surface and groundwater, the informal groundwater markets where farmers trade water have emerged in all provinces of Pakistan. Despite the considerable attention paid to the analysis of water markets in several countries, there is little evidence on the structure and implications of contractual agreements between the water users. This study includes buyers’ bargaining power in the contract choice model to estimate unbiased determinants of contract choice. The data was collected through a comprehensive survey of Punjab’s groundwater markets. Using several descriptive and econometric approaches, we find that the water markets in Pakistan are relatively competitive. A flat-rate water marketing contract is common in water-scarce regions, while a fuel-based contract is common in areas with large farmers. We find that buyers' bargaining power is primarily determined by an agent's ability to influence a joint decision between buyers and sellers. In addition, a seller's landholding size also influences the choice of contract, as fuel-based contracts are more likely to be offered to large farmers. The relative bargaining power of buyers influences choice of fuel-based contracts, although this offers lower profits to sellers. We find evidence of price discrimination in which relatively well-off buyers with a long contractual history with sellers may receive discounts in the form of fuel-based contracts. As contract choice may also determine the extent of water use, these findings have implications for environmental sustainability. Policy intervention to standardize groundwater marketing contracts can help reduce overexploitation of groundwater and environmental externalities and promote sustainable development.